ANALISIS PENERAPAN PROGRAM PENSIUN IURAN PASTI PADA DANA PENSIUN RUMAH SAKIT ISLAM - Zulfan Aulia Rahman, - (2019)
This research was conducted with the aim to find out the cause of the Islamic Hospital Pension Fund replacing the Defined Benefit Pension Program into a Defined Contribution and the impact on the estimated liability of the change in the pension program. This research was carried out using a skinative method and ethnometology approach. Based on the results of the discussion conducted, it shows that the factor of the Definite Contribution Pension Program is more profitable for the Employer because the company does not need to cover the lack of funds if the funds to pay the pension benefits due are less than the amount that should be paid to the participant. the participant who participates in the pension program, the amount of contributions to be paid by the employer to the Pension Fund on behalf of each participant depends on the initial ability of the establishment of the pension fund, and the period of employment before the pension program is implemented is not calculated in the payment of pension benefits. Whereas from the participant's point of view, the benefit pension program must be more profitable because participants know the amount of pension benefits to be received.